User‐engaged app development: Building better apps for the vineyard. Issue 1 (24th October 2017) - Given, Lisa M.; Deloire, Alain; Kelly, Wade; Paschke, Philip
ABSTRACT: Wine scientists and industry organisations are increasingly creating mobile web applications (apps) to support vineyard management and monitoring. While such tools are intended to improve wine industry practices, embedding user testing and user experience design in app development has not been implemented. User‐focused design is essential for determining the need for new apps, for assessing the effectiveness of existing tools and to optimize usability. This poster presents the results from an exploratory, interdisciplinary study drawing on information science theory and best practices to examine vineyard managers' and grape growers' experiences with two apps: Fit Vine and VitiCanopy. This study used hands‐on exploration of users' experiences with the apps in the vineyards to assess the usefulness of these tools from the users' perspective. Results include the need for consistent intuitive navigation, which is necessary to address a range of users' technological literacy levels; the need for help features to be integrated into the primary interface, which guides the users' experience; and, tools that provide added value to the work practices of users in vineyards in order to influence decision making. The results underscore the importance of involving wine industry members throughout the app‐ building process.